Authorship in copyright law: a critique in the context of the fourth industrial revolution - Dlamini, Simphiwe (University of the Free State, 2023)
This dissertation critically examines the demands for an amendment of the South African Copyright Act 98 of 1978 to bring it in line with modern times. It investigates authorship in copyright law from the perspective of the Fourth Industrial Revolution. This dissertation focuses specifically on artificial intelligence (AI) and its ability to generate copyrightable works under the Act. The growing use of AI technology inversely leads to the growing production of works generated by AI. These mechanically produced works share the same traits as those that, according to South African law, are entitled to copyright protection. As a result, there is currently uncertainty over who the author of such works is, because AI machines do not qualify as authors under the South African Copyright Act. This dissertation examines the definition of an author in the existing Copyright Act, as well as the requirements for authorship and copyright protection, in order to determine if this section of the Act needs to be amended to reflect the Fourth Industrial Revolution. To accomplish this, the dissertation investigates prominent South African intellectual property law textbooks as well as international sources that have conducted extensive research on the subject. The dissertation reveals the excessive use of artificial intelligence machinery and its products in the country and around the world. It demonstrates the growing need for legislation to govern such machinery in the country, as well as rules to regulate the usage of such technology and the copyrightable works it produces. The dissertation studies the nature of copyright in a work made by AI equipment nationwide and internationally, as well as how these machines will affect different areas in the country. An analysis of the requirements for copyright is provided, and it is argued that the present requirements for copyright cater to works generated by artificial intelligence even though these machines do not qualify as authors under the Act. Furthermore, the dissertation demonstrates how a lack of regulations in this regard will have a negative impact on specific areas, such as the country's education system. It indicates that South African legislation has not advanced sufficiently in comparison to other countries. The dissertation finds that the current Copyright Act is outdated and needs to be amended to account for AI generated works as well as AI authorship. Furthermore, legislation to oversee AI technology in the country should also be considered.
Dissertation(LL.M.(Mercantile Law))--University of the Free State, 2023
Keywords: Authorship; Copyright law; artificial intelligence; fourth industrial revolution